The Effecting Factors of Thrombolytic Therapy on Acut Myocardial Infarction Which Diagnosed In Emergency Department - Eren, Şevki Hakan; Yılmaz, Kerim; Korkmaz, İlhan; Aktaş, Can; Oğuztürk, Hakan; Alagözlü, Hakan (Fırat University, 2006)
Objectives: Myocardial reperfusion and early treatment of complications are the most effective factors for survey after AMI. In this study, we evaluated the effecting factors of thrombolytic theraphy in patients diagnosed with AMI at emergency department. Materials and Methods: Between the dates of January 2002 and January 2003, 168 patients diagnosed with AMI at emergency department in the Hospital of Medicine Faculty, Cumhuriyet University, Sivas, were included. Data about ages, types of AMI, attending time to the hospital after started chest pain, properties of thrombolytic theraphy were collected. Result: Seventy-nine patients with acute myocardial infarction were given thrombolytic theraphy. 89 (52.98%) patients weren’t given thrombolytic theraphy owing to some reasons. These reasons; 47 (52,81%) of these patients with delayed application to the hospital, 22 (24,72%) with non ST elevation myocardial infarction, 15 (16,85%) with delayed diagnosis at emergency department, 5 (5,62%) with thrombolytic theraphy contraindications. Conclusion: nearly a half of AMI patients weren’t given thrombolytic theraphy due to delayed attendance. Transporting difficulties have a major role in delayed attendance. Delayed diagnosis and contraindications for antithrombotic treatment have a minor role in administration of antithrombotic treatment ©2006, Fırat Üniversitesi, Tıp Fakültesi

Amaç: Miyokard enfarktüsünden sonraki sağ kalımı belirleyen başlıca faktörler koroner kan akımının hızlıca sağlanması ve komplikasyonların erken tedavisidir. Bu çalışmada, akut miyokard enfarktüsü (AMI) tanısı alan hastaların acil serviste trombolitik tedavi uygulamasını etkileyen faktörler incelendi. Gereç ve Yöntem: Ocak 2002-Ocak 2003 tarihleri arasında Cumhuriyet Üniversitesi Tıp Fakültesi Acil Servisi’nde AMI tanısı alan 168 hasta incelendi. Vakalar ile ilgili yaş, AMI tipleri, hastaneye başvuru zamanları ve trombolitik tedavi alan hastaların özelliklerine ait veriler toplandı. Bulgular: AMI tanısı alan bu hastaların 79’una (%47,02) trombolitik tedavi uygulanırken, 22 (%24.72) ST elevasyonu olmayan MI, 47 (%52.81) hastaneye geç başvuru, 15 (%16,85) tanı konulmadaki gecikme, 5 (%5,62) trombolitik tedavi kontrendikasyonu nedeniyle toplam 89 hastaya (%52.98) trombolitik tedavi uygulanamadı. Sonuç: Hastanemiz acil servisinde AMI tanısı alan hastaların yaklaşık yarısına geç başvuru nedeniyle trombolitik tedavi verilememektedir. Bu tedavi oranının düşüklüğünde hastaların hastaneye geç başvurmalarına neden olan ulaşım sorunu rol oynamaktadır. Tanı konulamama ve kontrendikasyonlar trombolitik tedaviyi az oranda etkilemektedir.©2006, Fırat Üniversitesi, Tıp Fakültesi
Acil Serviste Akut Miyokard Enfarktüsü Tanısı Almış Hastalarda Trombolitik Tedavi Uygulanmasını Etkileyen Faktörler